Near‐Infrared‐Excited Multicolor Afterglow in Carbon Dots‐Based Room‐Temperature Afterglow Materials. (9th September 2021) - Zheng, Yihao; Wei, Haopeng; Liang, Ping; Xu, Xiaokai; Zhang, Xingcai; Li, Huihong; Zhang, Chenlu; Hu, Chaofan; Zhang, Xuejie; Lei, Bingfu; Wong, Wai‐Yeung; Liu, Yingliang; et al.
Abstract: Room‐temperature afterglow (RTA) materials with long lifetime have shown tremendous application prospects in many fields. However, there is no general design strategy to construct near‐infrared (NIR)‐excited multicolor RTA materials. Herein, we report a universal approach based on the efficient radiative energy transfer that supports the reabsorption from upconversion materials (UMs) to carbon dots‐based RTA materials (CDAMs). Thus, the afterglow emission (blue, cyan, green, and orange) of various CDAMs can be activated by UMs under the NIR continuous‐wave laser excitation. The efficient radiative energy transfer ensured the persistent multicolor afterglow up to 7 s, 6 s, 5 s, and 0.5 s by naked eyes, respectively. Given the unusual afterglow properties, we demonstrated preliminary applications in fingerprint recognition and information security. This work provides a new avenue for the activation of NIR‐excited afterglow in CDAMs and will greatly expand the applications of RTA materials. Abstract : A universal method is developed to activate near‐infrared‐excited multicolor afterglow of carbon dots‐based RTA materials (CDAMs) through radiative energy transfer from NaYF4 :Yb, Tm upconversion materials (UMs). The resulting UM/CDAMs demonstrate bright and persistent afterglow from blue to orange under NIR CW laser excitation at 980 nm.